Contractor’s technology acceptance for firm sustainability performance - Bamgbaded, J. A.; Salimon, Maruf Gbadebo; Adeleke, A. Q.; Nasidi, Y. (KnE Social Sciences, 2019)
The construction industry’s contributions to Greenhouse gas emissions have generated several discussions among the construction stakeholders in recent times. Granted that the construction industry has been contributing significantly to the economy as well as employment in most countries for decades, the industry’s resource consumption is, at the same time, damaging to a sustained human environment. This paper empirically explored the organizational technology orientation and perceived organizational usefulness that could improve construction Malaysian construction firm’s sustainability performance. Close-ended structured copies of questionnaire survey were employed to collect data from large Malaysian construction firms, and Partial Least Squares-Structural Equation Modeling technique was used to analyze the 172 responses. The results indicated that both technology orientation and perceived organizational usefulness are capable of influencing the construction firms’ sustainability performance. The implication is that this study’s model can predict the sustainability performance of the sampled construction firms. Some implications for research and practice, as well as future recommendations, were highlighted.